The Philosophy of Quantum Physics - Friebe, Cord (Springer International Publishing, 2018)
This book provides a thorough and up-to-date introduction to the philosophy of quantum physics. Although quantum theory is renowned for its spectacular empirical successes, controversial discussion about how it should be understood continue to rage today. In this volume, the authors provide an overview of its numerous philosophical challenges: Do quantum objects violate the principle of causality? Are particles of the same type indistinguishable and therefore not individual entities? Do quantum objects retain their identity over time? How does a compound quantum system relate to its parts? These questions are answered here within different interpretational approaches to quantum theory. Finally, moving to Quantum Field Theory, we find that the problem of non-locality is exacerbated. Philosophy of quantum physics is aimed at philosophers with an interest in physics, while also serving to familiarize physicists with many of the essential philosophical questions of their subject.